2020
DOI: 10.3390/nu12040995
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Imbalance in Mice Results Primarily in Compensatory Gene Regulatory Responses in Kidney and Colon, but Not in Taste Tissue

Abstract: Renal excretion and sodium appetite provide the basis for sodium homeostasis. In both the kidney and tongue, the epithelial sodium channel (ENaC) is involved in sodium uptake and sensing. The diuretic drug amiloride is known to block ENaC, producing a mild natriuresis. However, amiloride is further reported to induce salt appetite in rodents after prolonged exposure as well as bitter taste impressions in humans. To examine how dietary sodium content and amiloride impact on sodium appetite, mice were subjected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 99 publications
1
8
0
Order By: Relevance
“…We quantified drinking behaviors that were driven by NaCl taste and "light taste." As expected from previous studies (Caloiero and Lundy, 2004;Raymond et al, 2017;Lossow et al, 2020a), Na 1 depletion via amiloride selfadministration resulted in a robust NaCl appetite. Na 1 -depleted mice preferred to optogenetically stimulate GAD65 1 TBCs, which resulted in overconsumption of illuminated H 2 O, despite exacerbating their Na 1 imbalance in the process.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…We quantified drinking behaviors that were driven by NaCl taste and "light taste." As expected from previous studies (Caloiero and Lundy, 2004;Raymond et al, 2017;Lossow et al, 2020a), Na 1 depletion via amiloride selfadministration resulted in a robust NaCl appetite. Na 1 -depleted mice preferred to optogenetically stimulate GAD65 1 TBCs, which resulted in overconsumption of illuminated H 2 O, despite exacerbating their Na 1 imbalance in the process.…”
Section: Discussionsupporting
confidence: 84%
“…Each trial was repeated on the following day with the bottles reversed to account for any inherent side preference. The protocol was presented at the 2017 Association for Chemoreception Sciences Annual Meeting (Raymond et al, 2017) and was recently validated by others (Lossow et al, 2020a) as a rapid method for inducing Na 1 appetite.…”
Section: The Rapid Induction Of Salt Appetite In Micementioning
confidence: 99%
“…The authors suggest that "oral microbiota composition deserves to be considered as an influencing variable when investigating perireceptor events involved in chemosensory processes". Lossow et al [4] studied the effect of changes in dietary salt content on mRNA expression for ENaC subunits in mouse taste buds. They found that mRNA levels were not affected either by low-salt or by high-salt diet.…”
Section: Na + Detectionmentioning
confidence: 99%
“…RAAS targets the renal nephron and the colon, where aldosterone affects sodium reabsorption through ENaC to match changes in sodium intake. Lossow et al [4] found that changes in dietary salt content in mice affected ENaC mRNA expression levels in kidney and distal colon. As reported above, they also analyzed ENaC expression in taste buds, since in this mammal ENaC works as sodium taste receptor.…”
Section: Na + Output Regulationmentioning
confidence: 99%
“…Although, sodium reabsorption by ENaC accounts for a comparatively small proportion (<5%), but it is the rate-limiting step and involved in final renal adjustment to sodium balance, ultimately regulating blood pressure. 8 Prostasin is believed to cause breakage of an inhibitory peptide from γ-ENaC in order to activate it intracellularly. 9 , 10 Studies on preeclamptic patients have also revealed that prostasin expression is present in the villi of primate and human placental cell lines.…”
mentioning
confidence: 99%